PERAN GURU DALAM MEMBERIKAN MOTIVASI BELAJAR SISWA SMA NEGERI 2 SENGAH TEMILA KABUPATEN LANDAK - Norelis, Victorlia; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aims to review the role of teachers in provide the motivation to learn students in SMAN 2 sengah temila Landak. The methodology used is descriptive of the qualitative study. Data source of this research is teachers and students class XII ips1, ips2, ips3 and The data is how teachers give attention, gift, reward, The consequent punishment of the in motivating of students to study the results of interviews with teachers and students. The Research shows that the teacher is done by teachers in providing student learning /increase the motivation is good, Gifts to by teachers to students is not optimal, This is only done for gifts on each semester and every increase class only, While the award by the teacher to student has been good enough, It was because the award by teachers for students and get a good appreciation, While the penalty to students done by teachers with right, Teachers give that penalty to students with advise, Scold and punish students in accordance with the students what it can be overcome by teachers.Keywords : The teacher motivate, student learning